2021
DOI: 10.3390/nano11092176
|View full text |Cite
|
Sign up to set email alerts
|

Dual Plasmon Resonances and Tunable Electric Field in Structure-Adjustable Au Nanoflowers for Improved SERS and Photocatalysis

Abstract: Flower-like metallic nanocrystals have shown great potential in the fields of nanophononics and energy conversion owing to their unique optical properties and particular structures. Herein, colloid Au nanoflowers with different numbers of petals were prepared by a steerable template process. The structure-adjustable Au nanoflowers possessed double plasmon resonances, tunable electric fields, and greatly enhanced SERS and photocatalytic activity. In the extinction spectra, Au nanoflowers had a strong electric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The self-cleaning process of the substrate is evidenced in two aspects. On the one hand, it has been demonstrated previously that Ag NPs can catalyze the degradation of small organic molecules [42]. On the other hand, the microstructure of PSS can significantly improve the light-capturing ability.…”
Section: Hydrophobicity Characterization and Self-cleaning Testmentioning
confidence: 99%
“…The self-cleaning process of the substrate is evidenced in two aspects. On the one hand, it has been demonstrated previously that Ag NPs can catalyze the degradation of small organic molecules [42]. On the other hand, the microstructure of PSS can significantly improve the light-capturing ability.…”
Section: Hydrophobicity Characterization and Self-cleaning Testmentioning
confidence: 99%
“…Nanoflowers have a representative structure of these 3-D plasmonic nanocrystals, presenting ultra-sensitive SERS signals. , For the construction of flower-like structures, many synthesis methods have been reported. For example, Guo et al proposed a rapid synthesis route to deposit Au nanoflowers on the surface of tin-doped indium oxide glass by the electrochemical deposition method .…”
Section: Introductionmentioning
confidence: 99%
“…High-performance substrates are the core of surface-enhanced Raman scattering (SERS) technologies and are a focus of extensive attention and research. To improve detection sensitivity, researchers have developed a variety of highly branched and/or hierarchical structures, including nanostars, nanoflowers, , and sea urchins. , High-efficiency Raman signal enhancement can be achieved by generating a strong plasmon resonance electric field at the edges and tips . At the same time, photocatalysis studies showed that high-index crystal face nanocrystals have a higher chemisorption energy, which is more conducive to plasma resonance, can theoretically achieve higher Raman signal enhancement amplification, and can improve the detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%